A Review of Mushrooms as a Potential Source of Dietary Vitamin D - Cardwell, Glenn (Nutrients, 2018)
When commonly consumed mushroom species are exposed to a source of ultraviolet (UV) radiation, such as sunlight or a UV lamp, they can generate nutritionally relevant amounts of vitamin D. The most common form of vitamin D in mushrooms is D(2), with lesser amounts of vitamins D(3) and D(4), while vitamin D(3) is the most common form in animal foods. Although the levels of vitamin D(2) in UV-exposed mushrooms may decrease with storage and cooking, if they are consumed before the ‘best-before’ date, vitamin D(2) level is likely to remain above 10 μg/100 g fresh weight, which is higher than the level in most vitamin D-containing foods and similar to the daily requirement of vitamin D recommended internationally. Worldwide mushroom consumption has increased markedly in the past four decades, and mushrooms have the potential to be the only non-animal, unfortified food source of vitamin D that can provide a substantial amount of vitamin D(2) in a single serve. This review examines the current information on the role of UV radiation in enhancing the concentration of vitamin D(2) in mushrooms, the effects of storage and cooking on vitamin D(2) content, and the bioavailability of vitamin D(2) from mushrooms.